Nutritional adequacy of meals consumed by adolescents of a philanthropic institution in Belo Horizonte (Research, Society and Development, 2021)
Considering the importance of an adequate diet in adolescence and that many young people spend most of the day in whole schools, the study aimed to evaluate the food consumption of adolescents from a philanthropic institution in Belo Horizonte, MG. About 600 adolescents, aged 13 to 17 years, participated in the study. The meals were qualitatively analyzed for 20 days using the method of Qualitative Evaluation of the Menu Preparations. And for quantitative analysis the direct weighing of the lunch was used during seven days. Per capita quantities were used for the snacks. The recommendations of the National School Feeding Program were used as a parameter to analyze the consumption of adolescents according to age, full time. It was found insufficient consumption of carbohydrates, proteins, lipids, energy, fiber, iron, magnesium, zinc, vitamin A, and vitamin C, for both age groups. The school environment acts as a means of promoting the health of adolescents. Given this context, there is a need for interventions in these populations in order to guarantee a balanced diet according to each age group, identifying nutritional diseases and groups at risk, thus promoting the health of adolescents.